Competition between conventional and Islamic banks in Malaysia revisited - Harkati, Rafik; Syed Jaafar Alhabshi, Syed Musa; Kassim, Salina (Emerald Group Publishing Ltd., 2020)
Purpose – This paper aims to assess the nature of competition between conventional and Islamic banks operating in Malaysia. It is an effort to enrich the existing literature by offering an empirical compromise on the differences in the results of studies related to competition between the two types of banks. Design/methodology/approach – Secondary data on all banks operating in Malaysia’s diversified banking sector is collected from the FitchConnect database for the period 2011-2017. A non-structural measure of competition (H-statistic) as informed by Panzar–Rosse is used to measure the competition between conventional and Islamic banks. Panel data analysis techniques are used to estimate H-statistic. Wald test for the market structure of perfect competition/monopoly is used to affirm the validity and consistency of the results. Findings – The findings of this study signify that the Malaysian banking sector operated under monopolistic competition during the period of study. The long-run equilibrium condition holds for the Malaysian banking sector. Competition among conventional banks is more intense than that among Islamic banks. Financial reform endeavours of Bank Negara Malaysia (BNM) along with the liberalisation wave of the financial system were successful in promoting competition, rendering the financial system contestable, resilient and dynamic. Practical implications – Regulators and policymakers may find the results beneficial in terms of rethinking the number of banks operating in the Islamic sector. The number of banks, however, is not the only determinant of competition in the banking sector. Implications of competition change for stability and risktaking behaviour of banks should be considered. Originality/value – Within the context of Malaysia’s diversified banking system, given the contradictory results reported in studies on competition, this study is an effort to provide a plausible middle ground. It suggests a possible answer as to why competition nature has not changed since the policy change initiatives of BNM, namely, banks merger, expansion of Islamic banking operation scope and liberalisation process.